Analisis Usahatani dan Nilai Tambah Bunga Melati Putih (Jasminum sambac) di Kecamatan Kandeman Kabupaten Batang - Tabita Tri Utami; Liska Simamora (Jurnal Ilmu Sosial dan Humaniora, 2023)
In order to increase the bargaining power of farmers and gain profits, it is necessary to shorten the trading chain and cultivate white jasmine flowers produced by the "Barokah" farmer group, Depok Village, Kandeman District. Processing of agricultural commodities is carried out to add value to agricultural products. The research objectives include: (1) knowing the costs, revenues, and profits of white jasmine farming and processing white jasmine flowers into flower ronce, (2) analyzing the added value generated from processing white jasmine flowers into flower ronce. Not all members of the population have the opportunity to be sampled in research. The sample is determined through non-probability sampling method. Sampling of farmers was carried out by purposive sampling while determining the sample of ronce craftsmen using the snowball sampling technique. The average total cost of producing jasmine flowers from the research results is Rp. 6,120,406/month. The average revenue is Rp. 1,138,333/month. White jasmine flower farmers suffered a loss of Rp. 4,992,072/month. The average income earned by ronce craftsmen is Rp.37,166,667/month, the average total production cost for ronce white jasmine flowers is Rp. 22,461,836/month, so that ronce jasmine craftsmen earn a profit of Rp. 14,704,831/month. The processing of white jasmine flowers into ronce jasmine flowers by flower ronce craftsmen also has an added value, namely Rp. 1,563,996.